Cell‐free DNA fetal fraction in twin gestations in single‐nucleotide polymorphism‐based noninvasive prenatal screening. (21st November 2019) - Hedriana, Herman; Martin, Kimberly; Saltzman, Daniel; Billings, Paul; Demko, Zachary; Benn, Peter
Abstract: Objectives: The performance of noninvasive prenatal screening (NIPS) for fetal aneuploidy in twin pregnancies is dependent on the amount of placentally derived cell‐free DNA, the "fetal fraction (FF), " present in maternal plasma. We report FF values in monozygotic (MZ) and dizygotic (DZ) pregnancies. Methods: We reviewed FF in pregnancies at 10 to 20 completed weeks gestational age based on single‐nucleotide polymorphism (SNP)‐based NIPS where zygosity was routinely established in twin pregnancies. The cohort included 121 446 (96.3%) singleton, 1454 (1.2%) MZ, and 3161 (2.5%) DZ pregnancies. For DZ twins, individual FFs were measured. Results: Combined FF for DZ and MZ fetuses were 35% and 26% greater than singletons, respectively. The individual FF contributions from each fetus in DZ twins were, on average, 32% less than singletons. FF in DZ twin pairs were moderately correlated (Pearson correlation coefficient.66). When a threshold of 2.8% FF was applied to define uninterpretable results, 1.7% (2102/121 446) of singletons, 0.8% (11/1454) of MZ pairs, and 5.6% (178/3161) of DZ pairs were uninterpretable. Conclusion: For optimal aneuploidy NIPS in twin pregnancies, zygosity should be established and in DZ twins FF for both fetuses should be determined to identify those cases where results can be reliably interpreted. Abstract : What's already known about this topic? Adequate cell‐free fetal DNA (fetal fraction [FF]) is essential for noninvasive prenatal screening. FFs in twin pregnancies may be higher or lower than that found in singleton pregnancies. What does this study add? In this large series of twin pregnancies, the average total FF was higher than for singletons but the per fetus FF was lower. There can be large differences in the two FFs in dizygotic twin pregnancies. Optimal prenatal aneuploidy screening in twin pregnancies requires information on both zygosity and the individual FFs.